BUILDING ENGLISH TEACHERS’ INSTRUCTIONAL ABILITY THROUGH T EACHERS’ SELF-EVALUATION AND CLINICAL SUPERVISON - Dewi Cahyaningrum; Kristiandi Kristiandi (University of Muhammadiyah Purwokerto, 2015)
Effective teaching conducted by teachers becomes one of the affecting factors toward students’ learning achievement. Effective teaching and learning here is teaching learning process that is locally and education-ally relevant and meaningful to the students. However, it is not easy for teachers to full fill this and that is why they need to do self-evaluation for keeping them moving with the process of adopting, adapting, and mediating the current views in teaching, current needs of the students and the current condition of the school. This paper proposes a practical model for providing clinical supervision to help teachers build their instructional ability by fostering teachers to do self-evaluation of their teaching. This paper also describes the challenges, problems, and practical solutions and strategies for helping teachers build their pedagogic compe-tence in terms of providing English instruction. Keywords: effective teaching, self-evaluation, and clinical supervision